Performance evaluation of WS2 as buffer and Sb2S3 as hole transport layer in CZTS solar cell by numerical simulation. Issue 5 (28th November 2022) - Riyad, Md. Nur Hossain; Sunny, Adil; Khatun, Most. Marzia; Rahman, Sabrina; Ahmed, Sheikh Rashel Al
Abstract: This study reports on performance enhancement of a Cu2 ZnSnS4 solar cell introducing Sb2 S3 as hole transport layer (HTL) along WS2 as buffer layer. We have investigated photovoltaic (PV) characteristics by utilizing SCAPS‐1D. A comparative analysis on PV performances between conventional CZTS/CdS and proposed Ni/Sb2 S3 /CZTS/WS2 /FTO/Al solar cells is presented. It is revealed that "spike like" band structure at the CZTS/WS2 interface having smaller conduction band offset makes it potential alternative to commonly used CdS buffer. This report also evaluates that the Sb2 S3 as an HTL inserted at the rear of CZTS enhances performances by reducing carrier recombination at back interface with appropriate band alignment. The impacts of thickness, carrier concentration of different layers, and bulk defect density in CZTS as well as the interface defects on cell outputs are analyzed. The influences of temperature, work function, and cell resistances are also examined. Optimum absorber thickness of 1.0 μm along doping density of 10 17  cm −3 is selected. A maximum efficiency of 30.63% is achieved for the optimized CZTS cell. Therefore, these results suggest that Sb2 S3 as HTL and WS2 as buffer layer can be employed effectively to develop highly efficient and low‐cost CZTS solar cells. Abstract : This study reports on performance enhancement in a Cu2 ZnSnS4 solar cell introducing Sb2 S3 as hole transport layer (HTL) along WS2 as buffer layer. We have investigated photovoltaic (PV) characteristics by utilizing SCAPS‐1D. A maximum efficiency of 30.63% is achieved for the optimized CZTS cell. Therefore, these results suggest that Sb2 S3 as HTL and WS2 as buffer layer can be employed effectively to develop highly efficient and low‐cost CZTS solar cells.